Long-Term Results of Cementless Total Hip Arthroplasty With Subtrochanteric Shortening Osteotomy in Crowe Type IV Developmental Dysplasia - Wang, Duan; Li, Ling-Li; Wang, Hao-Yang; Pei, Fu-Xing; Zhou, Zong-Ke (The Journal of arthroplasty, 2017)
When surgeons reconstruct hips with a high dislocation related to severe developmental dysplasia of the hip (DDH) in total hip arthroplasty (THA), archiving long-term stable implant fixation and improving patient function and satisfaction remain challenging. The purpose of this study was to evaluate the 10-year outcomes of transverse subtrochanteric shortening osteotomy in cementless, modular THA in Crowe type IV-Hartofilakidis type III DDH. We reviewed 62 patients (76 hips) who underwent cementless THA with transverse subtrochanteric shortening osteotomy from 2002-2010. There were 49 women and 13 men with a mean age of 38.8 years, all of whom had Crowe type IV DDH. Mean follow-up period was 10 years. The acetabular cup was implanted in placement of the anatomical hip center in all hips. The mean Harris Hip Score significantly improved from 38.8 points to 86.1 points. Similarly, modified Merle d'Aubigne and Postel Hip Score, Hip dysfunction and Osteoarthritis Outcome Score, and SF-12 also significantly improved. The mean limb length discrepancy was reduced from 4.3 cm to 1.0 cm. At mean follow-up of 10 years, there were 3 cases of postoperative dislocation, 2 cases of transient nerve palsy, 1 case of nonunion, and 4 cases of intraoperative fracture. Revision surgery was performed in 2 patients due to isolated loosening of acetabular component and femoral stem, respectively. Our data demonstrated that the cementless, modular THA combined with transverse subtrochanteric shortening osteotomy was an effective and reliable technique with high rates of successful fixation of the implants and satisfactory clinical outcomes.